PENGEMBANGAN BAHAN AJAR DIGITAL PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 12 MAKASSAR - Aminuddin, Hijrati; Haling, Abdul; Nurhikmah, Nurhikmah; Aminuddin, Rosihan (Department of Electrical Engineering, University of Patria Artha, 2021)
This study aims to develop e-module teaching materials using the Flipbook Maker application in educational economics subjects, to determine needs analysis, design development of e-module teaching materials using the Flipbook Maker application in class x economics subjects. The research was carried out using Research Development which is focused on developing e-module teaching materials for economic subjects using a valid, practical and effective flipbook application for students to use in the learning process. The development model used to produce quality, attractive, energy efficient, light weight and economical products refers to the (ADDIE) model, which consists of 5 stages, analysis, design, develop, and implementation. ), evaluation (evaluation) This study was carried out at 12 Makassar Public High School with a total of 20 students to see the practicality of e-module teaching materials, 2 experts to obtain the validity of the e-module developed and 20 students to see the level of effectiveness of the e-module - developed module. The results showed that the material expert validation was categorized as very valid and the media expert was categorized as very valid so that the teaching materials could be used in the learning process. The results of student responses indicate that student responses can be said to be very practical for field tests involving several students. This shows that the e-module developed has a practical appearance, the language and typeface used are clear and easy to read, the images in the module support learning material and learning concepts in the module according to the rpp of class x economics subjects. Furthermore, an analysis of the level of effectiveness of the e-module teaching materials was carried out using the students' post test in order to obtain the value in the effective category. Of the several stages used in the development of teaching materials using the flipbook application produced in this study, it is considered very good for use in economic subjects to achieve learning objectives.